Kinetics of Corrosion of BN–ZrO2–SiC Ceramics in Contact with Si‐Killed Steel. Issue 5 (6th February 2015) - Kumar, Abhishek; Thapliyal, Vivek; Robertson, David G. C.; Smith, Jeffrey D.
Abstract : The mechanism and kinetics of corrosion of BN–ZrO2 –SiC (MYCROSINT ® SO43) by molten Si‐killed steel was studied. Isothermal corrosion tests were performed for duration between 2 and 8 h. Refractory and steel composition and morphology changes were investigated. A kinetic model using process simulation software METSIM and thermochemical software FactSage was developed to understand refractory–steel interactions. The corrosion process showed a deviation from parabolic kinetics and was fitted by a combination of linear and parabolic terms. It was determined that corrosion of the BN–ZrO2 –SiC refractory was governed by dissolution of SiC and BN and removal of ZrO2 as the other phases were eliminated.